PENGEMBANGAN MEDIA TRAINER ROBOTIKA BERBASIS INTERNET OF THINGS DI SEKOLAH MENENGAH KEJURUAN - Gledis H, Adhe; Abd Djawad, Yasser; Jaya, Hendra (UNM Journal of Technology and Vocational, 2025)
The objective of this research is to design and develop an IoT-based robotics trainer media for vocational high schools (SMK) using the Research and Development (R&D) method with the 4D development model (Define, Design, Development, and Dissemination). In the Define stage, a needs analysis is conducted to determine relevant learning materials. The Design stage involves designing the trainer media, IoT web platform, and Student Worksheets (LKPD). During the Development stage, validation tests, practicality tests, and effectiveness tests are conducted, resulting in media that are valid, practical, and effective. The validation results indicate that the media have a very high validity level with an average percentage of 96.03%, covering aspects such as application/device, appearance, content, language, and presentation. Trials at various stages also yielded high scores, with an average score above 80%. The test results show that the media are highly practical and effective, with a gain value of 0.75, categorized as high, indicating an improvement in students' understanding. Overall, this learning media is relevant, easy to use, engaging, and effective in supporting IoT-based robotics learning.